Cytotoxic effect of purified amylase from Bacillus licheniformis on the MCF-7 cell line (Journal of the College of Basic Education, 2025)
One of the main causes of cancer-related death for women globally is breast cancer. Interest in physiologically active enzymes has grown as a result of the hunt for less harmful and alternative medicinal treatments. The study aims to evaluate the potential cytotoxic effect of purified amylase on the proliferation of MCF-7 human breast cancer cells. The study included the extraction and purification of the amylase enzyme from Bacillus licheniformis from clinical and environmental sources, as 13 isolates were obtained from 145 samples collected from Al-Kindi Hospital from November 2024 to January 2025. Bacterial colonies were randomly streaked on freshly prepared starch agar plate’s amylolytic strains and phenotypically assess Bacillus licheniformis ability to produce the amylase enzyme. The results showed that only 12 (95%) of Bacillus licheniformis could produce the amylase enzyme. Ammonium sulfate 80%, dialysis, and chromatography using Sephadex G150 and DEAE-cellulose columns were used to purify the amylase produced by Bacillus licheniformis. The purified amylase enzyme reduced the viability of MCF-7 breast cancer by 53.98% at a concentration of 150µg/ml.